1979
DOI: 10.1139/v79-095
|View full text |Cite
|
Sign up to set email alerts
|

Band resolution of optical spectra of solvated electrons in water, alcohols, and tetrahydrofuran

Abstract: The optical absorption spectra of solvated electrons in water, alcohols, and tetrahydrofuran are empirically resolved into two Gaussian bands and a continuun~ tail. The first Gaussian band covers most of the low energy side of the spectrum. The second Gaussian band lies at an energy slightly above that of the absorption maximum of the total spectrum. With the exception of teit-butyl alcohol, in water and alcohols the following were obserbed: ( 0 ) the first Gaussian bands have the same half-width, but the osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
0
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 0 publications
4
70
0
1
Order By: Relevance
“…14,15,16 This approach has provided a molecular level picture of the bulk solvated electron in methanol 17,18,19,20,21,22,23 that is consistent with experimental observations. 24,25,26,27,28,29,30 Despite the general qualitative agreement of experiment and theory, it was found that the measured position and the halfwidth of the optical spectrum of the solvated electron in methanol 26 is not satisfactorily predicted in simulations. 18 To remedy this inadequacy, a new electron-methanol molecule pseudopotential has been developed recently using static exchange pseudopotential theory.…”
Section: Introductionmentioning
confidence: 90%
“…14,15,16 This approach has provided a molecular level picture of the bulk solvated electron in methanol 17,18,19,20,21,22,23 that is consistent with experimental observations. 24,25,26,27,28,29,30 Despite the general qualitative agreement of experiment and theory, it was found that the measured position and the halfwidth of the optical spectrum of the solvated electron in methanol 26 is not satisfactorily predicted in simulations. 18 To remedy this inadequacy, a new electron-methanol molecule pseudopotential has been developed recently using static exchange pseudopotential theory.…”
Section: Introductionmentioning
confidence: 90%
“…1,2,3,4,5,6,7,8,9,10 The similarities and the differences of methanol as a solvent compared to water provide the main motivation for the scientific interest in studying electron solvation in methanol. A more complete understanding of electron solvation can be reached not only by varying the polar solvent but also by extending the investigations from bulk solvents to finite size solvated electron systems, negatively charged solvent clusters.…”
Section: Introductionmentioning
confidence: 99%
“…28 These simulations notably improved the position and the half-width of the optical spectrum of the solvated electron in bulk methanol in comparison with experiments. 3 This is important since, for the clusters experimentally assigned as having interior-bound electrons a strong detachment feature of the two-photon photoelectron spectrum using 1.55 eV excitation indicated the presence of a well-defined excited state that was accessible at 1.55 eV. 9 This would be consistent with the existence of a cluster-supported excited state similar to the broad absorption evident for the bulk solvated electron in methanol, peaked experimentally at 1.9 eV.…”
mentioning
confidence: 99%
“…2,3,4,5,6,7,8 Methanol, similarly to other polar solvents, localizes the excess electron in a solvent cavity surrounded by properly oriented methanol molecules. According to the ESR measurements of Kevan et al on excess electrons in low-temperature methanol glass, the first solvation shell contains 4±2 methanol molecules with an average hydroxyl hydrogen -electron distance of 2.3±0.15 Å.…”
Section: Introductionmentioning
confidence: 99%
“…3 The steadystate absorption spectrum of the solvated electron in methanol exhibits a broad, asymmetric band with a maximum at 1.95 eV. 4 The advance of ultrafast laser techniques made it also possible to investigate the relaxation dynamics of the excess electrons in methanol on the subpicosecond timescale. 5,6 More recently, resonance Raman experiments of Mathies et al…”
Section: Introductionmentioning
confidence: 99%